2013
DOI: 10.1055/s-0033-1350411
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of Sacroiliitis in Patients with Spondyloarthritis: Correlation with Anatomy and Histology

Abstract: Magnetic resonance imaging (MRI) of the sacroiliac joints (SIJs) has become established as a valuable modality for the early diagnosis of sacroiliitis in patients with inconclusive radiographic findings. Positive MRI findings have the same significance as a positive test for HLA-B27. Sacroiliitis is one of the key features of axial spondyloarthritis (SpA) in the classification proposed by the Assessments in Ankylosing Spondylitis (ASAS) group.?Early signs of sacroiliitis include enthesitis of articular fibroca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 33 publications
3
27
0
2
Order By: Relevance
“…Multiple studies, summarized in a recent systematic review, 9 have indicated that the occurrence of at least 3 positive physical examination signs in patients suspected of having SIJ dysfunction was highly predictive of their response to SIJB. In contrast to lumbar spine conditions in which imaging is considered to be critical for diagnosis, the painful SIJ is not associated with characteristic findings on plain radiographic or cross-sectional imaging with the exception being inflammatory findings in patients with seropositive 10 or seronegative 11 autoimmune spondyloarthropathies. At this time, plain radiographic and cross-sectional imaging are largely used to rule out other competing diagnoses, leaving SIJB as the de facto current standard for the confirmation of SIJ dysfunction preliminarily made based upon the history and physical exam.…”
Section: Introductionmentioning
confidence: 92%
“…Multiple studies, summarized in a recent systematic review, 9 have indicated that the occurrence of at least 3 positive physical examination signs in patients suspected of having SIJ dysfunction was highly predictive of their response to SIJB. In contrast to lumbar spine conditions in which imaging is considered to be critical for diagnosis, the painful SIJ is not associated with characteristic findings on plain radiographic or cross-sectional imaging with the exception being inflammatory findings in patients with seropositive 10 or seronegative 11 autoimmune spondyloarthropathies. At this time, plain radiographic and cross-sectional imaging are largely used to rule out other competing diagnoses, leaving SIJB as the de facto current standard for the confirmation of SIJ dysfunction preliminarily made based upon the history and physical exam.…”
Section: Introductionmentioning
confidence: 92%
“…The sacroiliac compartment can be divided into the anterior cartilaginous part of the joint with synovial tissue and a joint capsule and the posterior retroarticular space containing interosseous ligaments and fatty connective tissue [6] ( Fig. 1).…”
Section: Anatomy Of the Sacroiliac Joint And The Definition Of Needlementioning
confidence: 99%
“…Due to the complex and variable anatomy of the sacroiliac joint (SIJ), a local treatment remains a therapeutic and technical challenge [5,6]. SIJ injection is used for local pain relief in sacroiliitis in combination with first-line systemic therapies including nonsteroidal anti-inflammatory drugs (NSAIDs) and biologic agents [7].…”
Section: Introductionmentioning
confidence: 99%
“…To date, MRI is considered the most sensitive and specific imaging modality for diagnosing and evaluating SIJ inflammation in patients with early disease 4 . The introduction of biological drugs such as the tumor necrosis factor-α receptor blocker group and their beneficial effect on SpA resulted in an accelerated use of MRI for early detection of sacroiliitis 4,5 .…”
mentioning
confidence: 99%
“…The introduction of biological drugs such as the tumor necrosis factor-α receptor blocker group and their beneficial effect on SpA resulted in an accelerated use of MRI for early detection of sacroiliitis 4,5 . As a result, an increasing number of SIJ MRI are performed each year on patients with suspected sacroiliitis 6 .…”
mentioning
confidence: 99%